How does sanctioning context affect moral emotions and conformity? An examination of criminal identity negotiation in courts and restorative justice conferences - Keith, Shelley (Deviant behavior, 2022)
Recent research has shown how identities are affected by, and resistant to, reflected appraisals, or how individuals perceive others view them. Despite renewed interest in criminal identity negotiation, the implications that the sanctioning context has for affecting the identity verification process of offenders has been underresearched. Using a sample of 498 restorative justice and 475 court participants in the Australian Reintegrative Shaming Experiments (RISE), we discover that the effect of discrepancies between reflected appraisals and offender self-views on emotions and projected conformity vary by conference and court processing. These findings suggest that identity processes need to be considered when examining how offenders are sanctioned.